Analisis Minat Siswa Terhadap Karungut Di SDN 4 Menteng Kota Palangka Raya - Kistiana, Kistiana (FKIP, Universitas Palangka Raya, 2024)
This study aims to determine students' interest in Karungut at SDN 4 Menteng, Palangka Raya City. The questions to be answered in this study are: 1. How is the Karungut learning process at SDN 4 Menteng, Palangka Raya City, 2. What are the factors that support students' interest in karungut at SDN 4 Menteng, Palangka Raya City, 3. What are the factors that inhibit students' interest in karungut at SDN 4 Menteng, Palangka Raya City. To answer these questions, this study uses qualitative research with descriptive methods. Data collection used is observation and interviews. While in analyzing data, researcher uses interactive model analysis techniques. The results of this study are 1. Karungut learning once a week which is carried out on Wednesday accompanied by Manasai dance together from grade 1 to grade 6. Teacher who has expertise in the field of karungut and occasionally brings in people from the studio to play the kacapi, gong and gendang musical instruments. Karungut lyrics contain character education values, each karungut lyric has a meaning for students such as teaching about the value of life, respecting or honoring each other. 2. Supporting factors are the availability of adequate facilities and infrastructure for students such as Kacapi, Gendang, Gong, or Speakers to accompany karungut, there is enthusiasm and joy during karungut learning and the teacher inserts karungut when teaching local content, school support for karungut by holding extracurricular activities. 3. Factors that inhibit students' interest in karungut are that some students do not understand the Ngaju Dayak language because it is not their mother tongue, when learning karungut students do not understand the meaning of the karungut lyrics so that sometimes it is difficult for teachers to teach karungut. In addition, teacher is not yet able to play musical instruments and there are no special local content teachers who specialize in karungut. This can be seen based on the results of research that has been conducted by researcher that students have a special interest in the art of karungut, there is enthusiasm and joy when learning karungut is equipped with supporting facilities and infrastructure.